Infrastructure licensing as an instrument for urban resilience in informal settlements - Wiermann, Elinton (Latin American Journal of the Built Environment & Sustainability, 2025)
Objective – to assess how Brazilian law addresses the redevelopment of informal settlements, from the perspective of licensing essential urban infrastructure, with the aim of identifying whether current rules trigger municipalities to carry out redevelopment interventions, with the driving element being the need to adapt the informal city guided by resilience to change.Methodology – the research was developed in two interconnected stages: the first stage consisted of an exploratory and bibliographical investigation, based on books, articles and periodicals focused on Urban Law (especially from the perspective of the Federal Constitution of 1988, the City Statute, the Reurb Law, the National Guidelines for Basic Sanitation, and other related laws); and the second stage consisted of field research focused on the analysis of a specific Reurb process completed before the chosen Municipality (São Sebastião).Originality/Relevance – the research aims to fill a regulatory and technical gap regarding the need to implement urban infrastructure in informal urban centers, enabling them to withstand climate change and environmental disasters. The study's relevance lies in rethinking how the institution of urban land regularization, through the lens of urban infrastructure implementation, can be improved by incorporating elements of urban resilience.Results – it is concluded, at the end of the work, that the land regularization institute is regulated under a premise of granting broad discretion to the Public Power in relation to interventions in infrastructure to be carried out in informal urban centers, which when linked to the budgetary and institutional limitations of the Municipalities, tends to reduce the technology and investments directed to these interventions, suggesting the need to review the law, so that it has a footprint focused on urban resilience.Theoretical/Methodological Contributions – the research results were achieved by combining theoretical elements from two areas of knowledge (law and engineering), directed towards empirical research, which focused on the analysis of a certain urban land regularization process that reached a certain informal urban center located in an environmentally sensitive area of ​​a certain coastal municipality.Social and Environmental Contributions – the research findings can help the Public Administration reformulate public housing and land regularization policies, improving these policies and preparing informal cities for new climate challenges. It can also aid in the eventual revision of legislation governing land regularization, to regulate the licensing phase of urban infrastructure more specifically and in greater detail, thus ensuring compliance with the mandatory feasibility analysis for the installation of infrastructure geared toward urban resilience.
Keywords: Urban Land Regularization; Climate Change; Essential Urban Infrastructure